1998
DOI: 10.1148/radiology.207.3.9609900
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism: ancillary findings at spiral CT.

Abstract: Parenchymal findings may suggest further investigations when results of spiral CT are inconclusive in diagnosis of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
75
12
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 0 publications
14
75
12
6
Order By: Relevance
“…17,18 The frequency of sub-segmental PE is reported to be 6% . 19,20 In our study we observed six patients with sub-segmental emboli in the group of patients without syncope (10% ).…”
Section: Discussionmentioning
confidence: 59%
“…17,18 The frequency of sub-segmental PE is reported to be 6% . 19,20 In our study we observed six patients with sub-segmental emboli in the group of patients without syncope (10% ).…”
Section: Discussionmentioning
confidence: 59%
“…1). Spiral CT can also help detect indirect signs of PE such as pleural-based densities, linear densities, or plate-like atelectases, central or peripheral dilatation of pulmonary arteries, and pleural effusions [16] ( fig. 2).…”
Section: Image Interpretationmentioning
confidence: 99%
“…The only single parenchymal finding that is significantly associated with PE is a subpleural wedgeshaped density, commonly known as a Hampton9s hump ( fig. 2) [16]. Pitfalls in the interpretation of spiral CT arteriograms may be due to insufficient or heterogeneous vascular opacification in patients with cardiovascular and/or pulmonary comorbidity, breathing artifacts, and prominent lymphoid tissue in close vicinity to pulmonary arteries in the hilar area.…”
Section: Image Interpretationmentioning
confidence: 99%
“…[13,22,23] Klinik olarak pnömo-nik infiltrasyonlar ile pulmoner embolinin oluşturduğu dispne, taşipne, plörotik göğüs ağrısı ve hipoksemi gibi semptomlar birbirine oldukça benzerlik göstermektedir. Kabrhel ve ark.…”
Section: Discussionunclassified